Two pillared metal–organic frameworks comprising a long pillar ligand used as fluorescent sensors for nitrobenzene and heterogeneous catalysts for the Knoevenagel condensation reaction12. Issue 14 (15th March 2016) - Ghasempour, Hosein; Azhdari Tehrani, Alireza; Morsali, Ali; Wang, Jun; Junk, Peter C.
Abstract : Long-pillared zinc and cadmium–organic frameworks were synthesized and used as nitrobenzene sensors and heterogeneous catalysts for the Knoevenagel reaction. Abstract : Two new pillared zinc and cadmium–organic frameworks were synthesized by incorporating two different organic linkers, namely 2-aminoterephthalic acid as an oxygen-donor linker and N 4, N 4′-bis(pyridin-4-ylmethylene)-biphenyl-4, 4′-diamine as a long pillaring strut. The structures of these two frameworks were analyzed using X-ray crystallography, FT-IR spectroscopy, thermogravimetric and elemental analyses. Their structural features as well as their stability were studied. These two MOFs having the same organic composition and the same network topology but different inorganic nodes differ in their chemical stability. Also, these two frameworks respond differently to nitrobenzene when they are used as fluorescent sensors. Furthermore, the catalytic behavior of one of these frameworks toward the Knoevenagel condensation reaction was investigated.